Сили зображення між близько розділеними діелектриками - Goraichuk, T. V.; Il'chenko, L. G. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2003)
It is shown that the correct accounting of the space dispersion effects in the dielectrics (the intrinsical semiconductors) separated by a small vacuum interval leads to continuity of the image potential at the interfaces, making it possible to consider the charged state (microscopic structure) of the dielectric surfaces within the framework of the proposed model (real and hydroxylated silica surfaces).